Effects of Mayonnaise on Postprandial Serum Lutein/Zeaxanthin and β-Carotene Concentrations in Humans - MARUYAMA, Chizuko; USUDA, Mika; MASUDA, Yasunobu; TAKEDA, Sayaka; UEJI, Toshiyuki; HASEGAWA, Mineo; MARUSHIMA, Ranko (Journal of Nutritional Science and Vitaminology, 2009)
To clarify the effects of different physical forms of oil on postprandial serum lutein/zeaxanthin and β-carotene concentrations, we performed a vegetable meal loading test. Eighteen healthy subjects participated in the test, which consisted of broccoli as a control (CON) meal, broccoli with oil (OIL), and broccoli with mayonnaise (MS), consumed in random order. After collection of fasting blood samples, subjects consumed one of the three test meals. Fasting and postprandial changes in serum carotenoids were assessed 2, 4, and 6 h after ingestion of each test meal. Serum lutein/zeaxanthin and β-carotene concentrations were measured. Although no significant change was noted after the CON meal, the serum lutein/zeaxanthin concentration was higher at 4 h after consumption of the OIL meal, and at 2, 4 and 6 h after consumption of the MS meal, as compared with the fasting state. Serum β-carotene concentrations did not change after ingestion of either the CON or the OIL meal but were elevated 2, 4, and 6 h after MS ingestion as compared with the fasting state. The incremental areas under the curves (IAUCs) of serum lutein/zeaxanthin and β-carotene concentrations were higher after the MS meal than after the CON meal. IAUCs after the OIL meal exhibited no statistically significant differences from the CON and MS meals. We suggest that mayonnaise contributes to increase serum lutein/zeaxanthin and β-carotene concentrations when consumed with vegetables rich in these carotenoids.